The impact of the determinants of Tourism Villages on the Increase of the Human Development Index (HDI) in Indonesia - Ayu Esteka Sari (International Journal of Business and Quality Research, 2025)
This study aims to analyze the influence of the determinants of tourism village development on the increase of the Human Development Index (HDI) in Indonesia. The main focus of the research is on the determinants of tourist villages. The method used includes quantitative data analysis from various tourism villages in Indonesia to understand the relationship between the development of tourism villages and the improvement of HDI. The results of the study show that well-managed tourist villages can contribute significantly to the increase of HDI. Tourism villages have a significant effect on the Human Development Index (HDI) at the district level in Indonesia. The results of the study were obtained tourism villages have a positive effect on the Human Development Index (HDI) at the district level in Indonesia with a constant value of 4.202. Results of P>|t| 0.000 with a t calculation of 6.57